Ubiquitin-Fold Modifier 1 Acts as a Positive Regulator of Breast Cancer - Yoo, Hee Min; Park, Jong Ho; Jeon, Young Joo; Chung, Chin Ha (Frontiers in Endocrinology, 2015)
Oestrogen receptor-alpha (ERalpha) is a steroid hormone-sensitive transcription factor that plays a critical role in development of breast cancer. The binding of oestrogen to ERalpha triggers the recruitment of transcriptional co-activators as well as chromatin remodeling factors to oestrogen-responsive elements (ERE) of ERalpha target genes. This process is tightly associated with post-translational modifications (PTMs) of ERalpha and its co-activators for promotion of transcriptional activation, which leads to proliferation of a large subset of breast tumor cells. These PTMs include phosphorylation, acetylation, methylation, and conjugation by ubiquitin and ubiquitin-like proteins. Ubiquitin-fold modifier 1 (UFM1), one of ubiquitin-like proteins, has recently been shown to be ligated to activating signal co-integrator 1 (ASC1), which acts as a transcriptional co-activator of nuclear receptors. Here we discuss the mechanistic connection between ASC1 modification by UFM1 and ERalpha transactivation, and highlight how the interplay of these processes is involved in development of breast cancer. We also discuss potential use of UFM1-conjugating system as therapeutic targets against not only breast cancer but also other nuclear receptor-mediated cancers.